Reliability and failure rate analysis of pressure, vacuum and gravity sewer systems based on operating data. (March 2016) - Miszta-Kruk, Katarzyna
Abstract: This paper presents an assessment of operational reliability of elements of pressure, vacuum and gravity sewer systems, based on research focused on 7 different systems. The article discusses both traditional (gravity) sewer systems and unconventional sewer systems that are implemented on a large scale. The analysis and assessment were based on the data collected during investigations of real sewer systems over a period of 3 to 5 years. On the basis of the analyses, this paper presents the system elements that were found to be most susceptible to failure as well as the most common types of failure events. This analysis allowed the duration of the identified failure events to be determined and yielded a reliability assessment in the form of failure rates (λ) calculated for each highlighted element. An analysis of the results in terms of the functions of the objects most susceptible to failure allows one to assess their operational probability. Highlights: One investigate three kind of sewer systems in seven researched municipality. Each of the selected components in sewage system were assessed by failure analysis One examine changes in the level of failure intensity as the primary reliability index in the research. One confront the calculated failure rate values in three sewer systems and its components The lowest values in unconventional systems of analyzed index were achieved in pipes, and the highest ones in chambers.